2001
DOI: 10.1354/vp.38-5-540
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Initial Developmental Stages of Loma salmonae in Rainbow Trout (Oncorhynchus mykiss)

Abstract: Abstract. The intracellular microsporidian parasite Loma salmonae affects salmonids of the genus Oncorhynchus and is a significant cause of economic losses in pen-reared Chinook salmon (O. tshawytscha) in British Columbia. Loma salmonae infection is easily recognized by the xenomas that form in the gills, but early stages of infection are difficult to detect in histologic sections. In situ hybridization (ISH), using an L. salmonae-specific digoxigenin-labeled single-stranded DNA probe, was used to detect the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…However, placement of infectious spores directly on gills of Chinook did not result in infection Shaw et al (1998) found spores and possible sporoplasms in the intestinal epithelium shortly after exposure by standard histology. Sánchez et al (2001a) further confirmed this observation and found the parasite in epithelial cells and the lamina propria of the small intestine as early as 12 h post-exposure (p.e.) by using a Loma-specific in situ hybridisation (ISH) probe (Fig.…”
Section: Sequential Developmentsupporting
confidence: 71%
See 3 more Smart Citations
“…However, placement of infectious spores directly on gills of Chinook did not result in infection Shaw et al (1998) found spores and possible sporoplasms in the intestinal epithelium shortly after exposure by standard histology. Sánchez et al (2001a) further confirmed this observation and found the parasite in epithelial cells and the lamina propria of the small intestine as early as 12 h post-exposure (p.e.) by using a Loma-specific in situ hybridisation (ISH) probe (Fig.…”
Section: Sequential Developmentsupporting
confidence: 71%
“…The gut is the initial site of infection , Sánchez et al 2001a. Fish can be experimentally infected per os by intubation of spores ), infected tissue (Kent et al 1995, Speare et al 1998a or by co-habitation .…”
Section: Sequential Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, merogonial proliferation may presumably start in the cells that were initially infected. Sánchez et al (2001), using in situ hybridisation technique, have found that Loma salmonae migrates from mucosal epithelium to the lamina propria of the intestine before reaching the final destination in the gills. The dividing merogony stages were then detected within infected blood cells in the heart as early as day 2 post exposure (p.e.…”
Section: Route Of Fish Microsporidia From the Portal Of Entry To The mentioning
confidence: 99%